Peningkatan Kapasitas Pengelola Desa Wisata Sungai Langka dan Wiyono - Ridwansyah, Eksa; Siregar, Damara Saputra; Cahyo, Enggar Dwi; Astriyantika, Meyliana; Rahman, Budi (Jurnal Nusantara Mengabdi, 2024)
Purpose:The aim of this community service is to increase the capacity of the management of the Sungai Langka and Wiyono tourist villages. This goal-setting departs from the results of identifying and formulating the problems that have been found, namely: 1) the low ability of the community to prepare tourism packages based on local wisdom; 2) the low community ability to compile tourist guiding materials (storynomics); and 3) the low community ability to market tourism products in tourist villages.. Method: The method used is to conduct training in the form of 1) training on preparing wisdom-based tour packages; 2) training in compiling tourist guide materials (storynomics); and 3) digital marketing strategy training starting from websites, YouTube, Instagram, and brochures. Result: This condition results in a low level of visits and a less-than-optimal tourism experience in the tourism village The results of this community service are: 1) the preparation of tour packages based on local wisdom, starting with identifying tourism components, preparing the itinerary, and calculating the price of the tour package; 2) the identification of a number of tourist guide materials (storynomics), namely the story of legenda gunung sukma hilang, kuburan tua, pertanian dan perkebunan desa, and sulam kain jelujur; and 3) the creation of digital marketing media, starting with websites, YouTube, Instagram, and brochures. The conclusion obtained is that the target of this community service has been achieved so that it can increase the capacity of managers to manage the Sungai Langka and Wiyono tourist villages. Limitations: Often, limited funds and human resources hinder the implementation of capacity building programs optimally. Contributions: Capacity building for managers can empower local communities through training and education, so that they are more skilled in managing tourism.